(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2023)
The purpose of this paper is to examine the republican principle from a Constitutional perspective. Initially, a reconstruction of the main characteristics of the republican tradition will be made. Then, the republican principle will be analyzed from a theoretical point of view, as well as Supreme Court case law. As a conclusion, we will argue that the republican principle can have its reach broadened from a more popular and plebeian interpretation of the republican tradition.